STRATEGIC MANAGEMENT OF DECARBONIZATION TECHNOLOGIES: INTERNATIONAL ECONOMIC INTEGRATION AND INNOVATIVE DEVELOPMENT - Швець, Василь; Харін, Сергій; Папіж, Юлія (Ekonomìka ta suspìlʹstvo, 2025)
The article analyzes the latest data from the Copernicus Climate Change Observatory, which operates under the management of the European Commission, on exceptionally high air temperature anomalies in June 2025 in most of Europe. The article states that, under the existing conditions, in the interests of sustainable development of civilization, the imperative strategy for the development of the global economy is a decarbonization strategy, which involves growth using the broad innovation capabilities of the world's leading countries, their economic integration. In this regard, the need for targeted development of innovative technologies and investments is emphasized, taking into account the potential of universities and laboratories in Europe, the USA, Japan, other countries of the world, their financial resources for the implementation, in particular, of global projects in the following areas: research into thermonuclear energy, electromobility, development of promising battery technologies, wind and solar energy, use of hydropower. For the implementation of international innovative, the issues of strategic management effectiveness are of particular importance.